Identifying and Treating Hypercortisolism in Adrenal Incidentalomas - Mosley, Mary (MD Conference Express, 2014)
Studies have identified subclinical hypercortisolism in patients with adrenal incidentalomas, which is associated with greater rates of cardiovascular disease, type 2 diabetes mellitus, and mortality. This article discusses the genetics of bilateral macronodular adrenal hyperplasia, subclinical Cushing syndrome, as well as hypercortisolism in adrenal incidentaloma.